The blood mirror ebook - Weeks, Brent (Lightbringer, 2016)
Gavin Guile is missing, leaving Kip and his allies to face the White King's horde in the fourth novel of the NYT bestselling Lightbringer series by Brent Week's. When does an empire fall? The Seven Satrapies have collapsed into four-and those are falling before the White King's armies. Gavin Guile, ex-emperor, ex-Prism, ex-galley slave, formerly the one man who might have averted war, is now lost, broken, and trapped in a prison crafted by his own hands to hold a great magical genius. But Gavin has no magic at all. Worse, in this prison, Gavin may not be alone. Kip Guile will make a last, desperate attempt to stop the White King's growing horde. Karris White attempts to knit together an empire falling apart, helped only by her murderous and possibly treasonous father-in-law Andross Guile. Meanwhile, Teia's new talents will find a darker use-and the cost might be too much to bear. Together, they will fight to prevent a tainted empire from becoming something even worse. Devour this blockbuster epic fantasy series that had Peter V. Brett saying, "Brent Weeks is so good, it's starting to tick me off!"